Tracing The Role of Shamans and Their Rituals in the Sacred Hills of Bangka - Nopri Ismi (Universitas Islam Negeri Raden Fatah Palembang, 2024)
Shamans have an important role in maintaining various knowledge, values and norms related to the relationship between humans and humans and nature. They are tasked with protecting sacred areas while carrying out rituals full of local wisdom values which are one of the keys to forest conservation. This research aims to explore the role of shamans and their rituals on a number of sacred hills on Bangka Island. Such as Penyabung Hill, Maras Hill, Mangkol Hill, and Nenek Hill. The research method is descriptive qualitative. Qualitative data obtained through interviews, observation and documentation were analyzed using a qualitative descriptive approach. The research results show that shamans play an important role in providing opinions and considerations regarding important matters concerning the survival of village communities. Shamans have a special position in the culture of the people on Bangka Island, and are tasked with ensuring that all knowledge or wisdom related to the environment is implemented or adhered to by the community for generations. Overall, the rituals on the sacred hills have the same meaning, namely as a form of gratitude for the natural results that have been obtained. Rituals also contain a lot of educational, educational value, as well as a wise way of living with fellow humans and nature. The application of the shaman's role and values in rituals is important for dealing with various current environmental problems. Through rituals, people are reminded of their dependence on nature and their responsibility to protect it.